2023
DOI: 10.1038/s41598-023-29055-4
|View full text |Cite
|
Sign up to set email alerts
|

Zeolite A powder and beads from sugarcane bagasse fly ash modified with iron(III) oxide-hydroxide for lead adsorption

Abstract: The discharging of lead-contaminated wastewater is a concern because of its toxicity to living organisms and water quality resulting in dangerous water consumption, so it is highly recommended to remove lead from wastewater to be below water quality standards for a safe environment. Zeolite A sugarcane bagasse fly ash powder (ZB), zeolite A sugarcane bagasse fly ash powder mixed iron(III) oxide-hydroxide (ZBF), zeolite A sugarcane bagasse fly ash beads (ZBB), zeolite A sugarcane bagasse fly ash powder mixed ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 64 publications
7
8
0
Order By: Relevance
“…This could be attributed to the fact that the surface of the HAp/bentonite composite becomes saturated in the presence of a higher concentration of Cd(II), eventually, the Cd(II) ion tends to form an aggregate on the outer surface of the composite and deceased the surface area. Similar results have been reported by Praipipat et al (2023), and the study showed that the removal efficiency was decreased with increasing concentration 46 .
Figure 6 Interactive effect of parameters on the removal efficiency of Cd (II) ( a ) initial Cd concentration versus adsorbent dosage, ( b ) initial Cd concentration versus pH, ( c ) adsorbent dosage versus solution pH, and ( d ) adsorbent dosage versus contact time.
…”
Section: Resultssupporting
confidence: 91%
“…This could be attributed to the fact that the surface of the HAp/bentonite composite becomes saturated in the presence of a higher concentration of Cd(II), eventually, the Cd(II) ion tends to form an aggregate on the outer surface of the composite and deceased the surface area. Similar results have been reported by Praipipat et al (2023), and the study showed that the removal efficiency was decreased with increasing concentration 46 .
Figure 6 Interactive effect of parameters on the removal efficiency of Cd (II) ( a ) initial Cd concentration versus adsorbent dosage, ( b ) initial Cd concentration versus pH, ( c ) adsorbent dosage versus solution pH, and ( d ) adsorbent dosage versus contact time.
…”
Section: Resultssupporting
confidence: 91%
“…Initial lead concentrations from 10 to 70 mg/L of duck eggshell powder (DP), duck eggshell powder mixed iron (III) oxide-hydroxide (DPF), calcined duck eggshell powder (CDP), and calcined duck eggshell powder mixed iron (III) oxide-hydroxide (CDPF) were applied for the effect of initial lead concentration, and the results are shown in Fig. 7 d. Their lead removal efficiencies of duck eggshell materials were decreased with the increasing of initial lead concentration from 10 to 70 mg/L resulting from lack active sites for adsorb lead ions similarly found by other studies 6 , 14 , 28 , 39 , 45 , 51 , 56 . Lead removal efficiencies at 50 mg/L of DP, DPF, CDP, and CDPF were 98.35%, 98.94%, 99.04%, and 99.24%, respectively, and CDPF demonstrated a higher lead removal efficiency than others.…”
Section: Resultssupporting
confidence: 60%
“…Additionally, as the temperature rises, the decreasing ΔG°suggests that the adsorption of Pb 2 + and Hg 2 + becomes even more favorable at elevated temperatures. Calyx [4] naphthalene 29.15 [23] Chemically modified orange peel 73.53 [24] Orange peel 209.8 [12] Pomelo (Citrus maxima) fruit peels 47.18 [25] Waste orange peel 4.24 [26] Activated carbon 26.50 [27] Polypyrrole-Based Activated Carbon 50.00 [28] Lanthanum-based metal-organic framework-decorated polyaniline 185.19 [29] Waste orange peel (APK) 35.08 [30] OPF 2.30 [31] Orange peels 5.76 [32] sulphured orange peel 160.00 [ Unmodified orange peel 7.46 [35] Graphene oxide/FeeMn composite 33 [36] Egyptian raw mandarin peel 19.01 [37] Clay-based nanocomposites 52.18 [38] Raw orange peel 61.18 [39] Activated sago waste carbon 55.60 [40] Ag…”
Section: Thermodynamic Studiesmentioning
confidence: 99%